The Role of Industry Structure in Building Competitive Strategy and Competitive Advantage - Atika Atika; Arifin Ilham Manessa Gm; M. Ahzami Mubarak; Fill Ina Grace s; M Ali Akbar; Kuswanto Kuswanto; Dwi Rayana Siregar; Novita Sari Br Simanjuntak (The Future of Education Journal, 2026)
This study aims to analyze the role of industry structure in shaping competitive strategies and creating firms' competitive advantage. A qualitative approach was employed through a literature review and descriptive analysis of theories and concepts related to industry structure, competitive strategy, and competitive advantage. The findings indicate that industry structure, encompassing the intensity of competition, supplier bargaining power, buyer bargaining power, the threat of new entrants, and the threat of substitute products, plays a significant role in determining appropriate competitive strategies. Firms that are able to accurately understand the characteristics of their industry structure are more likely to formulate adaptive and sustainable competitive strategies. Therefore, a comprehensive understanding of industry structure is a critical factor in achieving and sustaining competitive advantage in an increasingly dynamic business environment.